The difference between registered natural head position and estimated natural head position in three dimensions. Issue 2 (February 2018) - Zhu, S.; Keeling, A.; Hsung, T.C.; Yang, Y.; Khambay, B.
Abstract: This study determined the intra-rater and inter-rater reliability of re-orientating three-dimensional (3D) facial images into the estimated natural head position. Three-dimensional facial images of 15 pre-surgical class III orthognathic patients were obtained and automatically re-orientated into natural head position (RNHP) using a 3D stereophotogrammetry system and in-house software. Six clinicians were asked to estimate the NHP of these patients (ENHP); they re-estimated five randomly selected 3D images after a 2-week interval. The differences in yaw, roll, pitch, and chin position between RNHP and ENHP were measured. For intra-rater reliability, the intra-class correlation coefficient (ICC) values ranged from 0.55 to 0.77, representing moderate reliability for roll, yaw, pitch, and chin position, while for inter-rater reliability, the ICC values ranged from 0.38 to 0.58, indicating poor to moderate reliability. The median difference between ENHP and RNHP was small for roll and yaw, but larger for pitch. There was a tendency for the clinicians to estimate NHP with the chin tipped more posteriorly (6.3 ± 5.2 mm) compared to RNHP, reducing the severity of the skeletal deformity in the anterior–posterior direction.